2020
DOI: 10.1016/j.tmrv.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Donor Deferral Due to Low Hemoglobin—An Updated Systematic Review

Abstract: Background/Objectives: Blood donors attending a donation session may be deferred from donating blood due to a failure to meet low hemoglobin (Hb) thresholds. This costs the blood donor service, and donors, valuable time and resources. In addition, donors who are deferred may have more symptoms and as a direct and/or indirect effect of their experience return rates of donors deferred for low Hb are reduced, even in repeat donors. It is therefore vital that low Hb deferral (LHD) is minimized. The aim of this upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 60 publications
2
22
1
Order By: Relevance
“…Scatter plot matrix identified body weight, sex, and uric acid as factors associated with hemoglobin level. Previous meta‐analyses have reported female sex and low body weight as factors of low hemoglobin level, 45 , 46 supporting our results. Uric acid also correlated with body weight ( r = 0.48) and sex ( r = −0.51) in our study, suggesting that uric acid was a confounding factor of body weight and sex.…”
Section: Discussionsupporting
confidence: 91%
“…Scatter plot matrix identified body weight, sex, and uric acid as factors associated with hemoglobin level. Previous meta‐analyses have reported female sex and low body weight as factors of low hemoglobin level, 45 , 46 supporting our results. Uric acid also correlated with body weight ( r = 0.48) and sex ( r = −0.51) in our study, suggesting that uric acid was a confounding factor of body weight and sex.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in their initial review of factors that affect a donor's risk of a low hemoglobin deferral, Smith and colleagues 2 identified 55 studies published between 1980 and 2012. In their recently published updated review, they found an additional 76 studies published between 2012 and 2019 3 . This demonstrates an expansion at an increasing rate in the knowledge of blood donor recruitment, behavior, and health issues.…”
Section: Introductionmentioning
confidence: 99%
“…This is made possible through voluntary or paid blood donation. 1 Consequently, the health and well‐being of blood donors are of paramount importance in transfusion medicine. Blood donor retention saves blood services institutions time and resources.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Efforts to retain donors and get adequate blood for transfusion purposes are hampered by donor deferrals for various reasons: low hemoglobin being the major reason worldwide. 1 Deferrals have cost and health care implications to blood services and a negative effect on the donors to give blood in the future. 1 For this reason, blood services have a responsibility to protect blood donors against developing anemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation